Development and bioassessment of high nutria-omega 5 cookies through animal modeling - Iqbal, Nida; Shabbir, Muhammad Asim; Khan, Moazzam Rafiq; Faisal, Muhammad Naeem (Frontiers in Nutrition, 2023)
The food industry generates a diverse range of waste byproducts during fruit processing, which can be repurposed to create functional foods and other valuable commodities. In this particular study, leftover agro-waste from pomegranate juice was valorized to obtain pomegranate seed oil (PSO), while utilizing sunflower oilseed cake to produce sunflower meal protein concentrate (SMPC). These two extracted components were then combined as ingredients to produce High Nutria Omega 5 (HNO5) cookies. To ensure the quality and viability of pomegranate seed oil, a comprehensive set of laboratory analytical procedures were employed to evaluate its characteristics. Subsequently, different ratios of pomegranate seed oil and sunflower meal protein concentrate were utilized to develop the HNO5 cookie products. These cookies underwent thorough sensory, physicochemical, storage, and proximate evaluations as well as efficacy studies to assess their overall nutritional quality and shelf-life properties. As compared to the control feed, the findings of the renal and liver functional tests indicated a favorable effect on ALT, AST, ALP, serum urea, creatinine, albumin, globulins, total proteins, and A/G ratio. The results revealed that PSO and SMPC cookies containing 15% PSO and 15% SMPC exhibited stability in numerous physicochemical and sensory assessments. The punicic acid in HNO5 cookies significantly reduced the effects of starvation in rats and progressively improved several metabolic processes and overall health profiles. Graphical Abstract